Смоленський князівський стіл з часів Володимира Мономаха - Писаренко, Ю.Г. (Археологія, 1989)
У статті простежуються етапи встановлення влади однієї з князівських ліній, започаткованих синами Ярослава Мудрого над Смоленською землею у другій половині XI — першій чверті XII ст. Исследуется вопрос о принадлежности власти над Смоленском во второй половине XI—первой четверти XII в. одной из княжеских линий наследников Ярослава Мудрого. Внимательный анализ автобиографической части «Поучения» князя Владимира Мономаха и привлечение данных летописи В. Н. Татищева показывают постоянную связь со Смоленском Владимира Всеволодовича Мономаха. Это опровергает вывод В. Л. Янина о том, что Смоленск был старшим наследственным уделом потомков князя Игоря Ярославича. Не находят подтверждения выводы ученого об официальном признании права Игоревичей на Смоленск Любечским съездом князей 1097 г., а также о непродолжительном княжении в городе Мстислава Игорева внука вначале XII в. Подтверждается ранее высказывавшаяся в литературе точка зрения о закреплении Смоленска в 1097 г. за Владимиром Мономахом. Генеалогическая ветвь князя Всеволода Ярославича имела законное право на княжение ее представителей в Смоленске, поскольку Всеволод после смерти отца Ярослава Мудрого, наряду со своими братьями Изяславом и Святославом, был одним из трех правителей «Русской земли», которые сами устанавливали это право. The paper is devoted to the problem which of the prince’s lines of Yaroslav the Wise successors was in power in Smolensk in the second half — first quarter of the 12th centuries. Thorough analysis of the autobiographical part of “Pouchenie" (Instructions) by prince Vladimir Monomakh as well as data from chronicles by V. N. Tatishchev have shown constant relations of Vladimir Vsevolodovich Monomakh with Smolensk. It permits rejecting the conclusion of V. L. Yanin that Smolensk was an elder hereditary independent principality of prince Igor Yaroslavich successors. Neither conclusions of this researcher are confirmed about official recognition of Igor successors’ right for Smolensk by the Lyubich congress of princes in 1097 as well as about a short-term power in Smolensk of Mstislav, Igor’s grandson early in the 12th century. Despite V. L. Yanin statement it appeared possible to confirm the standpoint (previously reported in literature) about the appointment on Smolensk in 1097 to Vladimir Monomakh. A question of genealogical branch of prince Vsevolod Yaroslavich had a legitimate right for its repre-sentatives to reign in Smolensk acquires an affirmative answer, becausse after the death Yaroslav the Wise Vsevolod as weel as his brothers Izyaslav and Svyatoslav (all sons of Yaroslav) was one of three rollers of the “Russian land”, who themselves established this right.